Effectiveness of Using E-books in Improving Language Skills among Kindergarten Students - Al-Swalha, Ali Suliman (Dirasat: Educational Sciences, 2020)
This study aims to determine the effectiveness of using electronic books in improving language skills of kindergarten students. The study followed a semi-experimental approach. The study sample consisted of (52) male and female students from kindergartens from the Jordanian capital, Amman, for the first semester of the academic year 2018/2019. The researcher prepared a language skill test consisting of (20) items. The study used an electronic book appropriate to the age group. There is a statistically significant difference between the mean scores of the grades of the two experimental groups taught using electronic books and the control group on the language skill test results, in favor of the experimental group. Moreover, there were statistically significant differences in language skills due to the interaction between the results of experimental group, the results of control group, and gender. This study recommends urging the use of the electronic books in teaching kindergarten students in light of the learning outcomes related to language skills. Further, encouraging kindergarten teachers to use the electronic books and benefit from them when teaching in learning centers. Furthermore, continuously holding training workshops for kindergarten teachers and focusing on the continuity of using the e-books in teaching.